Tinjauan Terhadap Parameter Dan Kualitas Kompos Organik Perusahaan Galangan Kapal Dengan Penggunaan Aktivator PROMI Dan Ecoenzymes - Marissa Ariny; Syadzadhiya Qothrunada Zakiyayasin Nisa (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
A shipyard company in Surabaya, which is one of the major industries, generates a large amount of organic waste, including food waste, vegetables, fruits, leaves, and wood. Although this organic waste is a potential source of humus and essential nutrients for the soil, most of it has not been optimally managed. Composting is an effective method to process organic waste into compost, which can reduce the negative impact of toxic compounds and pathogens on the environment. This research aims to evaluate the effectiveness of using two types of activators, namely PROMI and ecoenzymes, in accelerating the composting process and improving compost quality in accordance with SNI 19-7030-2004 standards. PROMI activator, which contains various microorganisms such as Trichoderma Harzianium, Pseudokoningii, and Aspergilus sp., and ecoenzymes, which is produced through fermentation of organic materials, were applied to shredded organic waste. The results showed that the use of both activators could accelerate the decomposition process of organic materials and produce high-quality compost within 21 days. With the final measurement results of both composts, both with PROMI and ecoenzymes treatment, the same pH and temperature values were obtained, namely pH 7 and temperature 30℃. Parameters such as pH, temperature, colour, smell, and texture of the compost are recorded periodically to ensure the composting process is going well. Thus, the use of PROMI and ecoenzymes activators not only increases composting efficiency but also provides a sustainable solution for organic waste management in the shipyard industry.